Crystallization by microwave energy: Effects on the survival probability of lithia-based glass ceramics - Diamantino, Pedro Santos [UNESP]; Rodrigues, Camila da Silva [UNESP]; Carvalho, Ana Beatriz Gomes de [UNESP]; Tribst, João Paulo Mendes; Riquieri, Hilton [UNESP]; Ramos, Nathália de Carvalho [UNESP]; Viegas, Diogo Miguel da Costa Cabecinha Pacheco; Bergamo, Edmara Tatiely Pedroso; Bonfante, Estevam Augusto; Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP] (FapUNIFESP (SciELO), 2024)
This study evaluated the survival probabilities of two lithia-based glass-ceramics after final crystallization in a microwave furnace using conventional crystallization as a reference. Disc-shaped samples of a lithium silicate (LS, Celtra Duo) and a lithium disilicate (LD, e.max CAD) were prepared and divided into two groups according to the crystallization method (n = 30): microwave (M) or conventional furnaces (C). The biaxial flexural strength test was used to determine the fatigue test profile and its parameters. Then, specimens were submitted to an accelerated life test (step stress) using three profile levels – mild, moderate, and aggressive – varying the load increments and the number of cycles until fracture (4 Hz). Survival data were used to calculate Weibull's beta (β) value and reliability of the assigned missions. Scanning electron microscopy was employed to analyze surface morphology, fracture characteristics, and failure patterns. Beta (β) values for the LS-C, LS-M, LD-C, and LD-M groups were 2.65, 0.25, 0.62, and 0.3, respectively. Similar reliability was observed in all groups after 50,000 cycles at 100 and 150 Mpa. At 200 Mpa, the crystallization method did not affect the reliability within LS or LD. However, LD showed greater reliability than LS when crystallized by microwave energy. Thus, microwave energy can be suggested as an alternative to the process of conventional lithia-based glass-ceramics crystallization without damaging their survival probabilities.
Keywords: Crystallization; Factures, Stress; Microwaves